Building an antimicrobial stewardship program: A narrative of six years under the Donabedian perspective - Fonseca Medeiros, Amanda; Margotto Bertollo, Caryne; Moreira Reis, Adriano Max; Costa, Monica Aparecida; Meireles Leite, Edna Marilea; da Silva Gonçalves, Simony; Nogueira Guimarães de Abreu, Mauro Henrique; Pedra de Souza, Renan; Parreiras Martins, Maria Auxiliadora (Frontiers in Pharmacology, 2023)
Introduction: Antimicrobial resistance (AMR) is increasing and represents one of the world's major challenges. AMR increase morbimortality, length of hospital stay and costs. Antimicrobial Stewardship Programs (ASP) is one of the key strategies to promote the rational use of antimicrobials since AMR is mostly driven by antimicrobial consumption. Objective: To describe the ASP implementation in a teaching hospital from the perspective of Donabedian quality assessment. Method: This was an observational descriptive study with secondary data collection, including document review of the ASP. The study setting was a general public 392-bed hospital. The ASP activities were performed by the hospital infection control committee (HICC), hospital pharmacy (HP) and diagnostic support laboratory (DSL). The description of the three services mainly involved in the ASP was based on a quality assessment model involving the dimensions of “structure”, “process” and “result” proposed by Donabedian. The distribution among dimensions was guided by the checklist of essential elements of the ASP that compose the Brazilian regulatory requirements. The checklist was applied in July, 2022, and the ASP results described from 2016 to 2021. Results: ASP actions have been gradually implemented since 2008 with the implementation of HICC and improved over the years. Regarding structure, the investments in technology were mapped, quantifying 26 computers and three software programs employed to computerize the ASP processes performed in specific physical areas by HICC, HP and DSL. Institutional guidelines used by HICC, HP and DSL guided clinical practices to operationalize ASP. The evaluation metrics improved for 10 indicators and worsened for four indicators. From the 60 items composing the checklist, the hospital met the requirements in 73.3% of the items (n=44). Conclusion: This study described the implementation of ASP in a teaching hospital, applying the Donabedian perspective. Although the hospital still does not have a classic ASP model, there were investments to improve structure, processes and results, aiming to comply with international guidelines. A high proportion of key elements of ASP in the hospital were followed according to the Brazilian regulatory requirements. Aspects related to antimicrobial consumption and the emergence of microbial resistance deserve further investigations.